Gender wage gap among highly educated workers: some evidence from Spain - Caparrós-Ruiz, Antonio (Emerald, 2024)
Purposes - This research provides new evidence concerning the drivers of the gender pay gap for highly educated workers in Spain. Design/Methodology/Approach - The study estimates wage models controlled for sample selection bias and applies the traditional Blinder-Oaxaca decomposition to examine the gender wage gap. Findings - The results show the existence of empirical evidence about the presence of gender wage gap among tertiary-educated workers. An interesting conclusion is that holding a master’s degree has a positive impact since it diminishes the unexplained component of the gender pay gap. Research limitations/implications - The survey used only analyses the labour insertion of tertiary-educated workers and its temporal scope does not allow us to examine the evolution of the gender wage gap throughout their careers. Social implications – The findings indicate that there is room for the implementation of policies aimed to diminish the gender inequality in the labour market even for highly educated workers, which could complement the current Spanish labour legislation regulating gender pay gap in firms. Originality/value – This article bridges two bodies of the economic literature: human capital returns and gender wage gap. The data used represent a contribution to the economic literature.
https://openpolicyfinder.jisc.ac.uk/id/publication/2827
Keywords: Mujeres - Salarios - España; Discriminación sexual en el trabajo - España; Tertiary education; Master's degree; Gender wage gap